Analisis Promosi, Harga, Kualitas Layanan, dan Kepercayaan terhadap Keputusan Pembelian Tiket Kapal - Miptahul Jannah Harahap; Andar Sri Sumantri; Sulistyowati Sulistyowati (Indonesian Maritime Researchers and Lecturers, 2025)
This research aims to analyze the partial and simultaneous influence of four independent variables—Ticket Price (X_1), Service Quality (X_2), Customer Trust (X_3), and Promotion (X_4)—on Ship Ticket Purchase Decisions (Y) at PT. PELNI Semarang Branch. Utilizing an associative quantitative method with a sample of 100 passenger respondents (N=100), the data were analyzed using multiple linear regression (SPSS 22.0). The model demonstrated a strong explanatory power, accounting for 55.7% of the variation in purchase decisions (Adjusted R^2 = 0.557). The t-test results indicate that all independent variables have a positive and significant influence on Purchase Decisions (all t_hitung > 1.9853). The Promotion variable (X_4) showed the strongest individual influence (β = 0.282, t=4.777), highlighting the critical nature of effective information dissemination and communication strategies in attracting and guiding mass maritime consumers. Customer Trust (X_3) and Service Quality (X_2) also proved highly significant, affirming the essential role of State-Owned Enterprise (BUMN) integrity and service reliability in mitigating perceived maritime travel risks. Managerial implications suggest PT. PELNI prioritizes enhancing Promotion through digital media and maintaining the fairness of Price setting, which remains a key consideration for this market segment.